Data pre-processing of website browsing record: An initial step for web page classification - Siti Hawa, Apandi; Jamaludin, Sallim; Rozlina, Mohamed (IEEE, 2021)
The Internet utilization has resulted in an increase in the number of web pages on the World Wide Web. The classification of web pages is required to organize the growing number of web pages. A web page classification system is proposed to be constructed using a deep learning algorithm. The initial step for web page classification is data pre-processing. The website browsing record is used as a dataset in this study. The raw dataset needs to be pre-processing to fetch the cleaned data by removing missing value data, redundant data, and error data. There are many steps in data pre-processing which include data cleaning and web content pre-processing. The main contribution of this paper is to investigate how to do data pre-processing on website browsing records that focusing on the Game and Online Video web pages that will be utilized as the dataset to construct the web page classification model. After doing the data pre-processing, the number of datasets will be reduced. This shows many datasets have been removed because it is inactive and not suitable to be used in this study as the dataset of Game and Online Video web pages.